Elites and institutional persistence - James A. Robinson (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
Particular sets of institutions, once they become established in a society, have a strong tendency to persist. In this paper I argue that understanding how elites form and reproduce is key to understanding the persistence of institutions over time. I illustrate this idea with a simple political economy theory of institutions and through examples from Liberia, the US, South Africa and Germany I show how elites influence institutions. To change institutions requires having an understanding of how reforms influence the preferences, capabilities and strategies of elites.
Keywords: D02; D72; N40; O43; 330; elites; political economy; persistence of institutions